Full employment or stagnation? - Culbertson, John Mathew (New York : McGraw-Hill, 1964)
The author's analysis of the causes of United States economic slack serves as the focal point for this animated discussion of the thinking underlying United States economic policy, the actions that were taken - and the errors that were made. "Full Employment or Stagnation?" provides a stimulus to and a basis for public discussion of these vital questions.
Includes bibliographical footnotes and index.
rpm 04/05/2018
Loans
Keywords: Full employment policies